CD45+CD326+ Cells are Predictive of Poor Prognosis in Non–Small Cell Lung Cancer Patients - Ishizawa, Kota; Yamanaka, Mie; Saiki, Yuriko; Miyauchi, Eisaku; Fukushige, Shinichi; Akaishi, Tetsuya; Asao, Atsuko; Mimori, Takahiro; Saito, Ryota; Tojo, Yutaka; Yamashita, Riu; Abe, Michiaki; et al. (Clinical cancer research, 2019)
The epithelial-to-mesenchymal transition, the major process by which some cancer cells convert from an epithelial phenotype to a mesenchymal one, has been suggested to drive chemo-resistance and/or metastasis in patients with cancer. However, only a few studies have demonstrated the presence of CD45/CD326 doubly-positive cells (CD45/CD326 DPC) in cancer. We deployed a combination of cell surface markers to elucidate the phenotypic heterogeneity in non-small cell lung cancer (NSCLC) cells and identified a new subpopulation that is doubly-positive for epithelial and non-epithelial cell-surface markers in both NSCLC cells and patients' malignant pleural effusions. We procured a total of 39 patients' samples, solid fresh lung cancer tissues from 21 patients and malignant pleural effusion samples from 18 others, and used FACS and fluorescence microscopy to check their surface markers. We also examined the mutations in patients with known acquired mutations. Our data revealed that 0.4% to 17.9% of the solid tumor tissue cells and a higher percentage of malignant pleural effusion cells harbored CD45/CD326 DPC expressing both epithelial and nonepithelial surface markers. We selected 3 mutation patients and genetically confirmed that the newly identified cell population really originated from cancer cells. We also found that higher proportions of CD45/CD326 DPC are significantly associated with poor prognosis. In conclusion, varying percentages of CD45/CD326 DPC exist in both solid cancer tissue and malignant pleural effusion in patients with NSCLC. This CD45/CD326 doubly-positive subpopulation can be an important key to clinical management of patients with NSCLC.